Respostas
respondido por:
11
a1=3
a2= 3 x 2 = 6
a3= 6 x 2 = 12
a4 = 12 x 2 = 24
Então a PG é = 3, 6, 12, 24
Espero ter ajudado
a2= 3 x 2 = 6
a3= 6 x 2 = 12
a4 = 12 x 2 = 24
Então a PG é = 3, 6, 12, 24
Espero ter ajudado
respondido por:
3
Boa tarde!
Dados:
a1 → 3
q → 2
n → 4
an → ?
_______________
An=a1·q⁽ⁿ⁻¹⁾
a4=3·2⁽⁴⁻¹⁾
a4=3·2³
a4=3·8
a4=24
_______________
a3=3·2⁽³⁻¹⁾
a3=3·2²
a3=3·4
a3=12
_______________
a2=3·2⁽²⁻¹⁾
a2=3·21
a2=3·2
a2=6
_______________
P.G → (3, 6, 12, 24)
_______________
Att;Guilherme Lima
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás